Concordance Between Active Partial Thromboplastin Time and Anti-Factor Xa Assays in Neurocritically Ill Patients Receiving Subcutaneous Heparin Prophylaxis. (July 2023) - Shinn, Grace; Berger, Karen; Roh, David; Doyle, Kevin; Boehme, Amelia K.; Connolly, Edward Sander; Park, Soojin; Agarwal, Sachin; Claassen, Jan; Der-Nigoghossian, Caroline
Background: Laboratory monitoring is not recommended when subcutaneous unfractionated heparin (SQ-UFH) is administered at prophylactic doses. However, aPTT prolongation and associated hemorrhage has been reported in the neurocritically ill. At our institution, Neuroscience Intensive Care Unit (Neuro-ICU) patients with prolonged aPTT are further evaluated with a follow up aPTT and anti-factor Xa. Purpose: The purpose of this study was to describe concordance between aPTT and anti-factor Xa in neurocritically ill patients receiving prophylactic SQ-UFH with evidence of aPTT prolongation. Methods: A retrospective chart review of adult patients admitted to the Neuro-ICU from June 2017 to June 2019 was performed. Patients were included if they received SQ-UFH with aPTT levels and at least one anti-factor Xa level drawn within one hour of each other. Concordance between paired aPTT and anti-factor Xa was evaluated using Cohen's weighted kappa. Results: Forty two patients with 56 paired aPTT and anti-factor Xa levels were included. The most prescribed SQ-UFH regimen was 5000 units every 8 hours (60.7%) and anti-factor Xa levels were drawn a median (IQR) of 5.7 (3.1-10.7) hours after the SQ-UFH dose. Only 16 (28.6%) pairs were in concordance. The analysis showed a weighted kappa of .09; 95% CI [−.05 to .22] indicating poor agreement. Conclusions: In neurocritically ill patients receiving prophylactic SQ-UFH with aPTT prolongation, there was poor concordance between aPTT and anti-factor Xa. This suggests that aPTT prolongation may not be solely driven by heparin activity and further evaluation of mechanistic drivers for coagulopathy in this population is necessary.